Estudio de prefactibilidad para la instalación de una planta de montaje de brazos hidráulicos aislados sobre camiones - Rodríguez Ugarte, José Luis (2016)
This prefeasibility study aims to build an assembly plant focused on insulated hydraulic aerial devices on trucks. These aerial devices are mainly used for maintenance of power lines, both urban and rural, and are used not only by energy distribution/transmission companies, but also by the Great Mining, which also gives maintenance to their own electricity lines.